ADVANCES IN RESEARCH ON GENOME EDITING CRISPR-CAS9 TECHNOLOGY - Shah, Syed Zawar; Rehman, Anum; Nasir, Hira; Asif, Azka; Tufail, Bakhtawar; Usama, Muhammad; Jabbar, Basit (Journal of Ayub Medical College Abbottabad, 2018)
The current era of genome engineering has been revolutionized by the evolution of a bacterial adaptive immune system, CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) into a radical technology that is making an expeditious progress in its mechanism, function and applicability. Utilizing a non-specific Cas9 nuclease and a sequence specific programmable CRISPR RNA (crRNA), this system cleaves the target DNA with high precision. With a vast potential for profound implications, CRISPR has emerged as a mainstream method for plausible genomic manipulations in a range of organisms owing to its simplicity, accuracy and speed. A modified form of CRISPR system, known as CRISPR/Cpf1 that employs a smaller and simpler endonuclease (Cpf1) than Cas9, can be used to overcome certain limitations of CRISPR/Cas9 system. Despite clear-cut innovative biological applications, this technology is challenged by off-target effects and associated risks, so safe and controlled implementation is needed to enable this emerging technique assist both biological research and translational applications. In this review, we intend to elucidate different aspects of CRISPR in the light of current advancements.